2014
DOI: 10.1073/pnas.1400446111
|View full text |Cite
|
Sign up to set email alerts
|

Preferential infection of human Ad5-specific CD4 T cells by HIV in Ad5 naturally exposed and recombinant Ad5-HIV vaccinated individuals

Abstract: Significance Efforts to develop an efficacious HIV vaccine have been unsuccessful to date. Efficacy trials have reported that recombinant Ad5 (rAd5)-HIV vaccines were not efficacious and unexpectedly associated with excess HIV infection in vaccine recipients. Understanding the underlying mechanisms is urgent and will further HIV vaccine design. By comparing human CD4 T cells specific to Ad5 and CMV, we report that natural exposure- or vaccine-induced Ad5-specific CD4 T cells are highly susceptible to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(48 citation statements)
references
References 30 publications
2
46
0
Order By: Relevance
“…Second, no HPV genes are expressed from the pseudogenomes, so there is no potential reduction in immunity to the target antigen because of immunodominance of an HPV viral antigen. Third, the recent cessation of an HIV trial (HVTN 502) highlighted the risk of potentiating HIV infection through the induction of HIV-susceptible CD4 ϩ T cells (56). Because ivag genetic vaccination with HPV vectors results in highly skewed CD8 ϩ T cell responses, it should minimize the risk of…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, no HPV genes are expressed from the pseudogenomes, so there is no potential reduction in immunity to the target antigen because of immunodominance of an HPV viral antigen. Third, the recent cessation of an HIV trial (HVTN 502) highlighted the risk of potentiating HIV infection through the induction of HIV-susceptible CD4 ϩ T cells (56). Because ivag genetic vaccination with HPV vectors results in highly skewed CD8 ϩ T cell responses, it should minimize the risk of…”
Section: Discussionmentioning
confidence: 99%
“…Occasionally, we observed a Ͻ2-fold increase in the level of CD4 ϩ T cells in HPV vector ivag-immunized groups, which is much less pronounced than the 20-fold increase in the level of CD8 ϩ T cells. Also, HPV vector ivag immunization did not induce expression of HIV coreceptor ␣4␤7 by cervicovaginal CD4 ϩ T cells (data not shown) (57,58), in contrast to marked induction of this coreceptor after vaccination with an adenovirus 5 vector (56). Finally, there are many human and animal papillomavirus types that are distinct serotypes.…”
Section: Figmentioning
confidence: 93%
“…CD4+ and CD8+ T-cell responses are directed towards epitopes within conserved regions of the virus, particularly the immunodominant hexon, [73][74][75][76] and these can be cross-reactive among different Ad species groups. [75,77] In recent years, a number of studies have demonstrated that pre-existing anti-vector T-cells are boosted in vivo [74,[77][78][79] and ex vivo following vaccination/stimulation with Ad vectors. [80,81] Furthermore, in addition to issues with pre-existing anti-vector NAbs limiting transgene expression, cellular immunity can also eliminate vectortransduced cells, having a negative impact on vaccine immunogenicity.…”
Section: Challenges and Limitations Associated With Adenoviral Vaccinesmentioning
confidence: 99%
“…The increased infection rate in men with baseline Ad5 seropositivity in Step is further supported by observed Ad5-specific cellular immune boosting in vaccines [21,22], data that Ad5 exposure of PBMC from Ad5-seropositive persons causes proliferation of mucosal-homed HIV-1-susceptible CD4 þ T cells [23], and the observation that Ad5-specific CD4 þ T cells (generated either by natural infection or rAd5 vaccination) appear to be more susceptible to infection than cytomegalovirus (CMV)-specific CD4 þ T cells [24]. However, none of the trials included a control vector-only group to distinguish between contributions of responses against rAd5 versus HIV-1 inserts.…”
Section: Role Of Preexisting Adenovirus Immunity In Increased Hiv-1 Imentioning
confidence: 82%